Parallel Computing: Accelerating Computational Science and Engineering ; proceedings (ProtoView, 2016)
About another 85 papers consider such topics as approximate inverse preconditioners for Krylov methods on heterogeneous parallel computers, simulating multiphase flows in the subsurface of supercomputers based on graphics processing units, a fault tolerant implementation of multi-level Monte Carlo methods, global communication schemes for the sparse grid combination technique, potentials and limitation for energy efficient auto-tuning, and a generic prototype to benchmark algorithms and data structures for hierarchical hybrid grids. (© Ringgold, Inc., Portland, OR)